Association of Circulating Spexin Levels with Metabolic and Hormonal Disturbances in Polycystic Ovary Syndrome Women and Normal Controls - Maliha Shameem; Taseer Ahmed Khan; Kausar Abbas Saldera; Hina Rashid; UfaqueBatool K. Samo (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
Objective: To evaluate and compare theserum Spexin levels in women with and without polycystic ovary syndrome (PCOS) and to find if there is any association of Spexin levels with metabolic and hormonal parameters among PCOS women. Methods: The case-control study was conducted from August 2021 till September 2022in the Physiology Department at Basic Medical Sciences Institute (BMSI), Jinnah Postgraduate Medical Center, Karachi and Infertility Clinic, Jinnah Postgraduate Medical Center, Karachi. The present study investigated 160 subjects in reproductive age group 15-45 years with 80 cases of PCOS diagnosed according to Rotterdam criteria and 80 controls without PCOS. The sample size was calculated using the Online Open Epi sample Size Calculator. IBM-SPSS version 20 was used to both store and analyze the data. Results: The levels of serum Spexin were found to be lower in patients with polycystic ovary syndrome 1.85±56ng/ml, compared to the levels of 2.65±50ng/ml in the healthy group (p<0.001). The metabolic markers such as BMI, fasting blood glucose, serum Insulin, Homeostatic Model Assessment for Insulin Resistance, Cholesterol and Triglycerides were found to be elevated in polycysticovary syndrome patients and were found to have a negative correlation with Spexin levels. High density lipoprotein was lower in polycystic ovary syndrome patients when compared to healthy controls, and indicated a positive link with Spexin. Also subjects with polycystic ovary syndrome had elevated levels of Luteinizing Hormone and Testosterone with Luteinizing Hormone negatively connected with Spexin. Conclusion: Decreased Spexin levels as compared to healthy peers was inversely associated with unfavorable metabolic and hormonal profiles in PCOS subjects, suggesting the inter-related roles of Spexin in the different metabolic and endocrine pathways of PCOS.